The European internal market thirty years on - Stefano Micossi (EconPol Forum, 2023)
Over the past thirty years, the Single European Market (SEM) has made impressive progress, growing to cover the main economic activities - from manufactured goods to all categories of services, net-work utilities and public services, public procurement, and the reconition of professional qualifica-tions, as well as the market for codified technology, which for long time was lagging behind. An ambi-tious initiative still underway is aiming to establish a fully-fledged online digital market. Implementation, however, has been wanting in a number of critical areas, notably affecting the reali-zation of the internal market for services. Apparently, the financial crises have impoverished the work-ing classes and seemingly drained the appetite for further market opening. As a result, the growth dividend of integration has been wea ker than hoped for. National policies have been insufficiently supportive, if not downright hostile, toward the goal of mar-ket integration. As a result, the past ten years have seen little progress in market opening within the Union, even in areas where there would be low-hanging fruit to pick - e.g., the completion of the SEM for natural gas and electricity. A new twist in EU policies has come from NextGenEU, an ambitious and richly funded program (EUR 750 billion to be deployed by 2026) to foster the digital and green transition in the EU. Its emphasis, however, seems to fall on domestic investment rather than cross-border integration. Herein lies a paradox: while the SEM would in itself be a powerful engine for higher growth and better employment prospects, without higher growth it is not likely to find sufficient support among Euro-pean citizens. This increases the risk that protectionism will return and that the Union will slide into a phase of regression
Keywords: 330